2021
DOI: 10.1002/cnr2.1401
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green versus technetium‐99m with blue dye for sentinel lymph node detection in early‐stage cervical cancer: A systematic review and meta‐analysis

Abstract: Background: The fluorescent dye indocyanine green (ICG) has emerged as a promising tracer for intraoperative detection of sentinel lymph nodes (SLNs) in early-stage cervical cancer. Although researchers suggest the SLN detection of ICG is equal to the more conventional combined approach of a radiotracer and blue dye, no consensus has been reached. Aims:We aimed to assess the differences in overall and bilateral SLN detection rates with ICG versus the combined approach, the radiotracer technetium-99m ( 99m Tc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Research suggests preoperative imaging with 99m Tc SPECT/CT can enhance the detection of true SLNs by guiding the surgeon to the right anatomical region, especially when SLNs are present at atypical locations [ 24 , 25 ] Another disadvantage of ICG is its rapid progression toward second echelons nodes, due to ICG’s small hydrodynamic diameter, undesirably leading to a higher number of (non-)SLNs removed compared to using 99m Tc [ 26 , 27 ]. Until now, studies comparing ICG with the more conventional method of a radiotracer and blue dye lack compelling evidence that fluorescence can safely replace the conventional method [ 28 , 29 ]. Hybrid modalities integrating the use of a radiotracer, including preoperative imaging, with real-time intraoperative fluorescence imaging could combine the advantages of both methods and are already being studied in other types of cancer [ 23 , 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests preoperative imaging with 99m Tc SPECT/CT can enhance the detection of true SLNs by guiding the surgeon to the right anatomical region, especially when SLNs are present at atypical locations [ 24 , 25 ] Another disadvantage of ICG is its rapid progression toward second echelons nodes, due to ICG’s small hydrodynamic diameter, undesirably leading to a higher number of (non-)SLNs removed compared to using 99m Tc [ 26 , 27 ]. Until now, studies comparing ICG with the more conventional method of a radiotracer and blue dye lack compelling evidence that fluorescence can safely replace the conventional method [ 28 , 29 ]. Hybrid modalities integrating the use of a radiotracer, including preoperative imaging, with real-time intraoperative fluorescence imaging could combine the advantages of both methods and are already being studied in other types of cancer [ 23 , 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective cohort studies reporting on the comparison of ICG versus 99m Tc combined with blue dye exist but are generally of insufficient quality, underpowered and potentially suffer from publication bias. After a systematic review and meta-analysis of the available literature comparing ICG with 99m Tc and blue dye, we found that the pooled bilateral detection rate with ICG appeared to be significantly higher 35. However, in adherence with the Grading of Recommendations, Assessment, Development, and Evaluation guidelines, the quality of evidence was too low to provide strong recommendations and directly omit the combined approach of a radiotracer and blue dye.…”
Section: Introductionmentioning
confidence: 89%
“…Currently, in both systematic reviews and European guidelines on cervical cancer, no consensus on the use of tracer has been reached, and both methods of SLN detection have been approved. [35][36][37] Before omitting any well-functioning and evidence-based procedure ( 99m Tc combined with blue dye), high-quality evidence on the performance of ICG in cervical cancer SLN mapping is needed. In the FILM trial by Frumovitz et al, it was stated: 'Although the combination of blue dye and radiocolloid might be better than blue dye alone and equivalent to indocyanine green in detecting sentinel nodes, no studies -either prospective or retrospective -have compared the combination of blue dye and radiocolloid with indocyanine green'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews and meta-analyses (35,(37)(38)(39)(40)(41) on SLN mapping technology concerning gynecological malignant tumors are concluded in Supplementary Table 1.…”
Section: Current Application Of Sentinel Lymph Node Mapping and Biops...mentioning
confidence: 99%